2016
DOI: 10.1038/srep29760
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxycurcuminoids but not curcumin upregulate neprilysin and can be applied to the prevention of Alzheimer’s disease

Abstract: Neprilysin (NEP) is the most important Aβ-degrading enzyme. Its expression level decreases with age and inversely correlated with amyloid accumulation, suggesting its correlation with the late-onset of Alzheimer’s disease. Recently, many reports showed that upregulating NEP level is a promising strategy in the prevention and therapy of Alzheimer’s disease. Here, we used a sensitive fluorescence-based Aβ digestion assay to screen 25 curcumin analogs for their ability to upregulate NEP activity. To our surprise,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 46 publications
(62 reference statements)
1
26
1
1
Order By: Relevance
“…Using, a sensitive fluorescence-based amyloid-β digestion assay, Chen and colleagues (2016) [98] screened 25 compounds for their ability to upregulate neprilysin (NEP) activity. To our surprise, four compounds, dihydroxylated curcumin, monohydroxylated demethoxycurcumin, and mono- and di-hydroxylated bisdemethoxycurcumin, increased NEP activity, while curcumin did not.…”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Using, a sensitive fluorescence-based amyloid-β digestion assay, Chen and colleagues (2016) [98] screened 25 compounds for their ability to upregulate neprilysin (NEP) activity. To our surprise, four compounds, dihydroxylated curcumin, monohydroxylated demethoxycurcumin, and mono- and di-hydroxylated bisdemethoxycurcumin, increased NEP activity, while curcumin did not.…”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasementioning
confidence: 99%
“…Finally, feeding monohydroxylated demethoxycurcumin (also named demethylcurcumin) or dihydroxylated bisdemethoxycurcumin (also named bisdemethylcurcumin) to APPswe/PS1dE9 double transgenic mice upregulated NEP levels in the brain and reduced Aβ accumulation in the hippocampus and cortex. These polyhydroxy curcuminoids offer hope in the prevention of AD [98]. …”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasementioning
confidence: 99%
“…They found that phenyl methoxy groups can contribute to the suppression of Aβ42 and to the suppression of APP. The researchers found that different curcuminoids presented different effects on the BACE1 expressions, for example, curcumin did not affect BACE1 mRNA (messenger RNA) and protein levels, AB12 suppressed BACE1 mRNA level, and AB9 suppressed Chen et al [54] found that poly-substituted hydroxylcurcuminoids are able to upregulate neprilysin, the most important Aβ-degrading enzyme. Thus, these compounds can be used to prevent AD.…”
Section: In Vitromentioning
confidence: 99%
“…When administered as the co-crystalized compound sacubitril/valsartan, the individual agents valsartan and LBQ657 dissociate, and have a blood elimination half-life of around 11 hours, reaching a plasma steady state concentration in three days. This makes sacubitril/valsartan suitable for twice daily dosing [63, 65, 66]. Pharmaceutical chemist and clinical pharmacologists have highly developed skills in drug synthesis and optimizing the pharmacodynamic effect of a drug, while physicians are uniquely qualified to evaluate the gaps in drug efficacy.…”
Section: What We Always Hoped For: a Pharmaceutical Breakthrough In Hmentioning
confidence: 99%
“…Accumulation of amyloid peptide closely mimics the phenotype of Alzheimer’s disease in a murine model [62] and, in fact, an active area of investigation in the treatment of Alzheimer’s disease is to employ therapeutic agents to augment neprilysin activity [63]. This raises the very real concern that in our quest to find the next ‘silver bullet’ for the treatment of HF, we may inadvertently be predisposing patients to neurological and ophthalmic dysfunction from the off-target effects that are inevitable for any therapeutic agent, and occasionally underappreciated until the stage of post-marketing surveillance of the drug by the Food and Drug Administration Adverse Event Reporting System (FAERS).…”
Section: Neprilysin Inhibition With An Angiotensin Receptor Antagonismentioning
confidence: 99%